2002
DOI: 10.1108/00012530210448235
|View full text |Cite
|
Sign up to set email alerts
|

The costs and benefits of the Internet as a marketing and communications tool: the attitudes, perceptions and experiences within the non‐profit environmental sector in Scotland

Abstract: Discusses the findings of a study investigating the attitudes, perceptions and experiences of Scottish non‐profit environmental organisations and the costs and benefits of the Internet as a marketing and communications tool. Aims to ascertain whether the size of the organisation and the level of Internet use determines the perceptions and beliefs of non‐profit organisations within the environmental sector in Scotland and whether these factors also determines the costs and benefits experienced by Internet users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…These include the environmental industries sector (EIS; DTI, 2003), a young but rapidly expanding sector engaged in the provision of market and quasi-market environmental goods and services, such as pollution control, waste management and clean technology production. They also include activities of the widely recognised public and notfor-profit sectors engaged in environmental management and in the provision of environment-related public goods and services, such as environmental regulation and conservation (Illingworth et al, 2002;ERM, 2000;McCulloch et al, 1996). A further group of activities within the core category are those directly focused on turning environmental amenity value into a marketable commodity, such as nature-based tourism and some environmental media activity (SNH, 1998).…”
Section: Defining Environment-and Natural Heritage-related Activitiesmentioning
confidence: 99%
“…These include the environmental industries sector (EIS; DTI, 2003), a young but rapidly expanding sector engaged in the provision of market and quasi-market environmental goods and services, such as pollution control, waste management and clean technology production. They also include activities of the widely recognised public and notfor-profit sectors engaged in environmental management and in the provision of environment-related public goods and services, such as environmental regulation and conservation (Illingworth et al, 2002;ERM, 2000;McCulloch et al, 1996). A further group of activities within the core category are those directly focused on turning environmental amenity value into a marketable commodity, such as nature-based tourism and some environmental media activity (SNH, 1998).…”
Section: Defining Environment-and Natural Heritage-related Activitiesmentioning
confidence: 99%
“…Each activity paired two participants to work with the researcher. "Pair programming" is a coding methodology often used in industry and education (Cockburn & Williams, 2001;Van Toll, Lee, & Ahlswede, 2007) to improve quality of work, and perhaps learning. For this study the pairs did not tend to spontaneously collaborate on the programming tasks.…”
Section: Open Play and Independent Experimentationmentioning
confidence: 99%
“…Among the papers, Gupta and Jambhekar (2002) describe how a customer focus approach can be developed in marketing library and information services. Illingworth et al (2002) have investigated the attitudes, perceptions and experiences of Scottish non-profit environmental organisations and the costs and benefits of the Internet as a marketing and communications tool. Overall, the organisations found that the Internet was a low-cost, high-benefit marketing solution, but attitudinal factors affect the level of use by small organisations.…”
Section: Marketing and Public Relationsmentioning
confidence: 99%